Odpowiedź :
a) 5 - (-2) : [tex]\frac{1}{2}[/tex] = 5 + 2 * 2 = 5 + 4 = 9
b) (-3 - 7) + 5 : [tex]\frac{1}{5}[/tex] = -10 + 5 * 5 = -10 + 25 = 15
c) [-5 - (-2)] : [tex]\frac{1}{2}[/tex] = (-5 + 2) * 2 = -3 * 2 = -6
d) [(-3 - 7) + 5] : [tex]\frac{1}{5}[/tex] = (-10 + 5) * 5 = -5 * 5 = -25
e) [5 - (-2)] * [tex]\frac{1}{2}[/tex] = (5 + 2) * [tex]\frac{1}{2}[/tex] = 7 * [tex]\frac{1}{2}[/tex] = 3[tex]\frac{1}{2}[/tex]
f) [(-3 - 7) + 5] * [tex]\frac{1}{5}[/tex] = (-10 + 5) * [tex]\frac{1}{5}[/tex] = -5 * [tex]\frac{1}{5}[/tex] = -1
g) [tex]\frac{5 - (-2)}{2}[/tex] = [tex]\frac{5 + 2}{2}[/tex] = [tex]\frac{7}{2}[/tex] = 7 * [tex]\frac{1}{2}[/tex] = 3[tex]\frac{1}{2}[/tex]
h) [tex]\frac{-3 - 7 : 5}{5}[/tex] = [tex]\frac{-3-\frac{7}{5} }{5}[/tex] = [tex]\frac{\frac{-15}{5} -\frac{7}{5} }{5}[/tex] = [tex]\frac{\frac{-22}{5} }{5}[/tex] = [tex]\frac{-22}{5}[/tex] * [tex]\frac{1}{5}[/tex] = -[tex]\frac{22}{5}[/tex]
i) - [tex]\frac{-12-3+7}{4}[/tex] = - [tex]\frac{-8}{4}[/tex] = -(-2) = 2